Mesh size control in forming an Ag/AgO nano-network structure for transparent conducting application. (5th January 2022) - Chen, Jia-Wei; Yang, Shaobo; Li, Chia-Hao; Huang, Yang-Yi; Chen, Chen-Hua; Yang, C C
Abstract: The variation behaviors of the morphology, transmission, and sheet resistance of the surface Ag/AgO nano-network (NNW) structures fabricated under different illumination conditions and with different Ag deposition thicknesses and thermal annealing temperatures in forming initial Ag nanoparticles (NPs) are studied. Generally, an NNW structure with a smaller mesh size or a denser branch distribution has a lower transmission and a lower sheet resistance level. Under the fabrication condition of a broader illumination spectrum, a lower thermal annealing temperature, or a thicker Ag deposition, we can obtain an NNW structure of a smaller mesh size. The mesh size of an NNW structure is basically controlled by the seed density of Brownian tree (BT) at the beginning of light illumination. A BT seed can be formed through a stronger local localized surface plasmon resonance for accelerating Ag oxidation in a certain region. Once an Ag/AgO BT seed is formed, the surrounding Ag NPs are reorganized to form the branches of a BT. Multiple BTs are connected to form a large-area NNW structure, which can serve as a transparent conductor. Under the fabrication conditions of a broader illumination spectrum, 3 nm Ag deposition, and 100 °C thermal annealing, we can implement an NNW structure to achieve ∼1.15 μ m in mesh size, ∼90 Ω sq −1 in sheet resistance, and 93%–77% in transmittance within the wavelength range between 370 and 700 nm.